1988
DOI: 10.1016/s0886-3350(88)80033-6
|View full text |Cite
|
Sign up to set email alerts
|

Control of intraocular pressure in glaucomatous eyes after extracapsular cataract extraction with intraocular lens implantation

Abstract: Two hundred sixty eyes of 195 patients having extracapsular cataract extraction (ECCE) with insertion of a posterior chamber intraocular lens were studied retrospectively. Of these cases, 160 eyes had preexisting glaucoma while 100 had no ocular pathology except for cataract. Intraocular pressure decreased significantly after ECCE in both groups and slowly returned to baseline within two years. The average postoperative visual acuity was better in the control group than in the glaucoma group. Patients with gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Several theories have been hypothesized to explain these findings, mostly involving anatomical or biochemical alterations induced by the surgical intervention [44]. Similarly, several studies have also found that IOP is reduced, on average, in POAG patients after cataract surgery [45][46][47][48][49][50]51 ].…”
Section: Cataract Surgery Alonementioning
confidence: 99%
See 2 more Smart Citations
“…Several theories have been hypothesized to explain these findings, mostly involving anatomical or biochemical alterations induced by the surgical intervention [44]. Similarly, several studies have also found that IOP is reduced, on average, in POAG patients after cataract surgery [45][46][47][48][49][50]51 ].…”
Section: Cataract Surgery Alonementioning
confidence: 99%
“…Previous studies had shown that IOP may be reduced by approximately 2 mmHg at 1 year after extracapsular cataract extraction [21,[45][46], and more recent studies with cataract extraction by phacoemulsification have confirmed these findings [47][48][49][50]51 ]. Interestingly, one large study with up to 10 years follow-up has shown that the decrease in IOP after cataract surgery may be a function of the IOP at baseline (i.e., the greater the IOP at baseline, the greater the IOP reduction after cataract surgery) so that in a treated POAG patient the effect of cataract surgery on IOP may be limited to 1-2 mmHg of IOP reduction [51 ].…”
Section: Cataract Surgery Alonementioning
confidence: 99%
See 1 more Smart Citation
“…Postop¬ eratively, the IOP decreased significantly in the group with glaucoma and in the control group and had again reached the initial values 2 years later. 40 McCartney et al41 pointed out that this effect caused by cataract surgery was lower after additional lens implantation. In comparison, the re¬ sults of our study revealed an average decrease in IOP of 3.7 mm Hg even 1 year after cataract surgery alone.…”
Section: Surgical Techniquementioning
confidence: 99%
“…A previous evidencebased metaanalysis review concluded that phacoemulsification may have a modest IOP-lowering effect in patients with open-angle glaucoma, 4 although most long-term studies published to date are clinical case series without untreated control groups. [5][6][7][8][9] Many such studies, by lacking multiple preoperative IOP readings, are subject to the possibility of regression to the mean, resulting in an exaggeration of the IOP-lowering effect of phacoemulsification alone.…”
mentioning
confidence: 99%